2001
DOI: 10.1103/physrevlett.86.324
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the Singlet-Dimer Ground State in anS=1Antiferromagnetic Bond Alternating Chain

Abstract: Susceptibility, ESR, and magnetization measurements have been performed on single crystals of an S = 1 bond alternating chain compound: [Ni(333-tet) (mu-NO2)] (ClO4) (333-tet = N,N'-bis(3-aminopropyl)propane-1,3-diamine) and the compound doped with a small amount of Zn. We observed an anomalous angular dependence in the Zn-doped sample. These results are well explained by the model based on the valence-bond solid picture for the singlet-dimer phase. The picture implies that the free spins of S = 1 with a posit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
64
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(67 citation statements)
references
References 17 publications
3
64
0
Order By: Relevance
“…When −∞ < α < 0 in the S = 1 system, on the other hand, the trivial dimer phase around α ∼ 0 is shown to be smoothly connected to the S = 2 Haldane phase which appears in the limit α → −∞ [20]. Experimentally, using some nickel chain compounds which are regarded as the S = 1 bond-alternating Heisenberg system, magnetic susceptibility, magnetization, and ESR measurements were performed [23,25,26,27,28]. From the comparison between the experimental and numerical results, the strength of the bond-alternation α was evaluated and it was concluded that some compounds are in the singlet-dimer phase [25,26,28] and the other compound is close to the gapless point [23,27].…”
Section: Introductionmentioning
confidence: 99%
“…When −∞ < α < 0 in the S = 1 system, on the other hand, the trivial dimer phase around α ∼ 0 is shown to be smoothly connected to the S = 2 Haldane phase which appears in the limit α → −∞ [20]. Experimentally, using some nickel chain compounds which are regarded as the S = 1 bond-alternating Heisenberg system, magnetic susceptibility, magnetization, and ESR measurements were performed [23,25,26,27,28]. From the comparison between the experimental and numerical results, the strength of the bond-alternation α was evaluated and it was concluded that some compounds are in the singlet-dimer phase [25,26,28] and the other compound is close to the gapless point [23,27].…”
Section: Introductionmentioning
confidence: 99%
“…NTENP has an energy gap between the singlet ground state and the first excited triplet [12], and exhibits an LRO above H c [13,14]. Unlike in NDMAP, the principal axis of the Ni 2 ions in NTENP is nearly parallel to the chain direction.…”
mentioning
confidence: 99%
“…The inversion centers are situated in the nitrito groups rather than the Ni 2 ions, so that no staggered components of the magnetic moments are expected to be retained. The critical fields H c parallel and perpendicular to the chain direction are 9.3 and 12.4 T, respectively [12].…”
mentioning
confidence: 99%
See 2 more Smart Citations